2018
DOI: 10.17352/2455-3484.000025
|View full text |Cite
|
Sign up to set email alerts
|

Gaming Disorder and Effects of Gaming on Health: An Overview

Abstract: Introduction: A video game is any software program that can be played on a computing device, such as a personal computer, gaming console or mobile phone. Video games are age and gender friendly, very popular but like other pleasurable endeavors, can have adverse consequences, which are reviewed. Aims: This review focuses on the effects of gaming on health, compares gaming with other disorders and opens further discussion on gaming disorder. The overall goal is to explore gaming disorder prevention methods incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 14 publications
(14 reference statements)
1
17
0
6
Order By: Relevance
“…In studies focused on the effects of internet games on different parts of the brain have shown behavioral and cognitive changes such as improved orientation, increased attention span, improved visual and environmental attention [3]. The negative effects are listed as addiction to the game, increased anger and aggression, and other physical and psychological effects, where risks outweigh the benefits such as increased eye coordination among other positive aspects [4].…”
Section: Introductionmentioning
confidence: 99%
“…In studies focused on the effects of internet games on different parts of the brain have shown behavioral and cognitive changes such as improved orientation, increased attention span, improved visual and environmental attention [3]. The negative effects are listed as addiction to the game, increased anger and aggression, and other physical and psychological effects, where risks outweigh the benefits such as increased eye coordination among other positive aspects [4].…”
Section: Introductionmentioning
confidence: 99%
“…Engaging in gaming can be time-consuming and has been associated with increased consumption of sweet drinks (Turel et al 2017), but maintaining a healthy diet is essential. Also, excessive online gaming is associated with physical inactivity, obesity, musculoskeletal problems (pain in hands, wrist, neck, and back), and visual problems (Ayenigbara 2018;Zirek et al 2020). At present, there is much uncertainty as to what will happen regarding the COVID-19 pandemic, due to the ever-changing characteristics of the virus (Lippi et al 2020).…”
mentioning
confidence: 99%
“…Mustafaoğlu ve arkadaşlarının yaptığı çalışmada, dijital oyun oynamanın, omurga, omuz ve el bileğinde kas iskelet sistemi problemlerine neden olabileceği belirtilmiştir (12). Bir başka çalışmada aşırı ve/veya problematik internet kullanımının ve oyun oynamanın boyun ve sırt ağrısına neden olabileceği vurgulanmıştır (13). Bu çalışmanın sonucunda ise, diğer çalışmalardan farklı olarak İOOB tanısı olan adölesanların oyun oynama sırasında kas iskelet sistemi semptomlarına önem vermedikleri tespit edilmiştir.…”
Section: Bulgularunclassified